Respostas

2014-05-23T02:18:01-03:00
X² +5x +6=0
a= 1  b= 5  c=6
Δ= b² -4 .a.c
Δ=(5)² -4 . 1 . 6
Δ=25 - 24
Δ= 1
x= \frac{-b+- \sqrt{Δ} }{2.a}
x= \frac{-(5)+- \sqrt{1} }{2.1}
x'= \frac{-5+1}{2}
x'= \frac{-4}{2}
x'= -2
x''= \frac{-5-1}{2}
x''= \frac{-6}{2}
x''= -3
1 5 1
2014-05-23T07:18:40-03:00
X² + 5X + 6 = 0

Δ = 5² - 4 . 1 . 6
Δ = 25 - 24
Δ = 1

X = - 5 + √1                                                     X = - 5 - √1                                                         2 . 1                                                              2 . 1   

X = - 5 + 1                           ou                          X = - 5 - 1 
          2                                                                     2
X = - 2                                                              X = - 3                         
 
1 5 1
Desconsidere a resposta acima
X² + 5X + 6 = 0

Δ = 5² - 4 . 1 . 6
Δ = 25 - 24
Δ = 1

X = - 5 + √1 X = - 5 - √1 2 . 1 2 . 1

X = - 5 + 1 ou X = - 5 - 1
2 2
X = - 2 X = - 3